Konsep Produksi dan Uang Menurut Ibnu Kholdun dan Relevansinya pada Perekonomian di Indonesia - Wahyudi, Catur; Bawono, Anton (Innovative: Journal Of Social Science Research, 2024)
Many world economic scientists recognize the work of Ibn Khaldun, one of the leading Muslim figures. He is a highly developed figure and has contributed to the agenda of world civilization, especially Muslims. The purpose of this study is to study two of Ibn Khaldun's many works related to deeper economic issues, namely the theory of money and the theory of production, and how these things relate to the Indonesian economy. In this article, what is discussed is the figure of someone who has contributed to science through his widely distributed works and has been used as a reference by several writers of the next generation. Therefore, the librarian research method is used. The study found that although Ibn Khaldun said that money does not always have to consist of gold and silver, both are used to determine the value of money. The government has an obligation to maintain the value of the money printed. The government sets prices regularly. To be used in economic activities, money must flow, roll, and rotate in society. Therefore, Ibn Khaldun's view of money is a flow view and not a stock view. Money, on the other hand, can be used as a means of payment or to buy goods and services. not only to calculate price standards.